A systematic review of Structural Contingency Theory and structure-environment-effectiveness relationship - Ziaulhaq, Aqsa; Sohail, Mishal (International Journal of Psychosocial Rehabilitation, 2021)
This paper aims to review structural contingency theory and the relationship between structure-environment effectiveness. This review paper is a conceptual paper based on qualitative research analysis. This review paper explained and reviewed 30 articles from the 21st century about structural contingency theory. After reviewing different papers on Structural Contingency theory, it was found that organizations’ structure should be flexible in external contingencies, especially in loose, dynamic environments. The study proposes that SCT can help organizational development by fitting between the structure and multiple contingencies. The Fit between organic structure and high environmental uncertainty and the Fit between mechanical structure and low environmental uncertainty can exist simultaneously in an organization. The uncertain external environment is one of the most important contingencies in which an organization must respond. An organization’s external environment as a set of factors could influence the organizational system’s functioning This paper provided a guideline to companies for the practical usage of SCT and stated that SCT provides companies with an opportunity to evaluate the contingencies and source of effective structure for organizations.